Economic Activities of Craft Cooperatives in Tambov Province from 1921 to 1924 - G. S. Makhrachev (Научный диалог, 2025)
This article explores the regional specifics of organizing economic activities among craft cooperatives and their unions during the early stages of the revival of craft cooperation in the NEP era. The timeframe under consideration corresponds to the initial phase following the end of War Communism. The study identifies distinctive features of the operations of consolidated artisans by the conclusion of this period. Furthermore, it analyzes the status of district and provincial special unions that were active from 1921 to 1922. Several factors hindering the establishment of a cooperative system were identified, including a weak financial foundation for the newly formed unions, their loose organizational structure, a shortage of skilled professionals, an inability to operate under market conditions, and organizational missteps by board members. A separate analysis is devoted to the period of 1923 to 1924, during which a severe crisis in cooperative development occurred. The author concludes that this crisis stemmed from both objective factors (such as changes in the territorial boundaries of the province and the nationwide economic crisis of 1923) and subjective factors (including numerous miscalculations by local cooperative leadership). It is demonstrated that as a result of this process, the only remaining district union of craft cooperation in the province was dissolved, and craft cooperatives virtually disappeared from mixed unions. The article emphasizes that many fraudulent cooperatives also ceased to exist during this time.